Blood flow restriction alters motor unit behavior during resistance exercise - Fatela, P.; Mendonca, G. V.; Prieto Veloso, A.; Avela, J.; Mil-Homens, P. (International Journal of Sports Medicine, 2019)
We aimed to determine whether blood flow restriction (BFR) alters the characteristics of individual motor units during low-intensity (LI) exercise. Eight men (26.0±3.8yrs) performed 5 sets of 15 knee extensions at 20% of one-repetition maximum (with and without BFR). Maximal isometric voluntary contractions (MVC) were performed before and after exercise to quantify force decrement. Submaximal isometric voluntary contractions were additionally performed for 18s, matching trapezoidal target-force trajectories at 40% pre-MVC. EMG activity was recorded from the vastus lateralis muscle. Then, signals were decomposed to extract motor unit recruitment threshold, firing rates and action potential amplitudes (MUAP). Force decrement was only seen after LI BFR exercise (-20.5%; p<0.05). LI BFR exercise also induced greater decrements in the linear slope coefficient of the regression lines between motor unit recruitment threshold and firing rate (BFR: -165.1±120.4 vs. non-BFR: -44.4±33.1%, p<0.05). Finally, there was a notable shift towards higher values of firing rate and MUAP amplitude post-LI BFR exercise. Taken together, our data indicate that LI BFR exercise increases the activity of motor units with higher MUAP amplitude. They also indicate that motor units with similar MUAP amplitudes become activated at higher firing rates post-LI BFR exercise.